A critical evaluation of coral Ba/Ca, Mn/Ca and Y/Ca ratios as indicators of terrestrial input: New data from the Great Barrier Reef, Australia. (15th September 2018) - Lewis, Stephen E.; Lough, Janice M.; Cantin, Neal E.; Matson, Eric G.; Kinsley, Les; Bainbridge, Zoe T.; Brodie, Jon E.
Abstract: Coral trace element proxies of terrestrial runoff are widely applied to document and quantify historical changes in river discharge, constituent loads and land disturbance. However, some studies show poor replication between trace element records where cores from multiple coral colonies have been analyzed. Conflicting interpretations also exist on the environmental variable the coral trace element proxy is recording. Indeed, few studies have examined trace element behavior in the estuarine mixing zone that influence the coral records and only limited data on river discharge and constituent loads are available to validate the proxy records of terrestrial runoff. This study examined the behavior of Barium (Ba), Manganese (Mn) and Yttrium (Y) in the Burdekin River estuarine mixing zone, north-eastern Australia during several flood events and investigated the ability of coral Ba/Ca, Mn/Ca and Y/Ca ratios to record the variability of measured Burdekin River discharge and suspended sediment loads along a transect of replicate coral cores (10 cores from 5 locations). The results show limited evidence for Ba desorption from suspended sediments in the estuarine mixing zone while considerable desorption of Mn over a wide salinity mixing gradient was evident. Y showed evidence of removal in the initial mixing zone of the estuary (0–5 PSU) but displayed a relatively flat pattern thereafter indicating that it was not diluted by seawater mixing. The coral trace element records generally showed poor agreement within sites and the Ba/Ca ratios in some corals did not respond to regional river discharge, although coral luminescent lines were present in all cores and were significantly correlated with each other and Burdekin River discharge. While it was difficult to disentangle the influence of Burdekin River discharge and suspended sediment loads on the coral Ba/Ca proxy, several lines of evidence point towards discharge as the major contributor to this proxy in this region. A combination of factors likely influence the coral Ba/Ca ratio including an as yet undetermined physiological mechanism possibly related to crystallography or species, distance of the coral to the river mouth, variability in river discharge (including both annual totals and peaks, and local influences), variability in sediment load, the behavior of trace elements in the estuarine mixing zone, the hydrodynamics of flood plumes in the marine environment and the water depth of the coral. While the coral Mn/Ca and Y/Ca ratios did not respond to Burdekin River discharge events, the considerable desorption of Mn and the elevated Y throughout the estuarine mixing zone shows some promise in their ability to record long-term changes in suspended sediment loading and large terrestrial disturbances. Future studies examining coral records of terrestrial runoff should examine trace element behavior in the river estuarine mixing zone of influence, establish a correlation between the trace element and river discharge (such as luminescent lines) and demonstrate replication between different coral colonies.